A new application of terahertz time-domain absorption spectra in luminescent complexes: characterization of the C–H⋯π weak interactions in Cu(i) complexes. Issue 29 (7th July 2021) - Sun, Zhen-Zhou; Zhu, Ning; Pan, Xun; Wang, Guo; Li, Zhong-Feng; Xin, Xiu-Lan; Han, Hong-Liang; Feng, Yue-Bing; Jin, Qiong-Hua; Yang, Yu-Ping; Yang, Wei
Abstract : Using terahertz spectra to characterize the C–H⋯π weak interactions in the Cu(i ) luminescent complexes. Abstract : Six Cu(i ) complexes, [Cu(2, 3- f )(bdppmapy)]BF4 (1 ), [Cu(2, 3- f )(bdppmapy)]ClO4 (2 ), [Cu(2, 3- f )(bdppmapy)]CF3 SO3 (3 ), [Cu(imidazo[4, 5- f ])(bdppmapy)]BF4 (4 ), [Cu(imidazo[4, 5- f ])(bdppmapy)]ClO4 (5 ), and [Cu(imidazo[4, 5- f ])(bdppmapy)]CF3 SO3 ·MeOH (6·MeOH ) (bdppmapy = N, N -bis[(diphenylphosphino)methyl]-2-pyridinamine, 2, 3- f = pyrazine[2, 3- f ][1, 10]-phenanthroline, and imidazo[4, 5- f ] = 1 H -imidazo[4, 5- f ][1, 10]-phenanthroline), have been synthesized to explore the effects of counteranions on their crystal structures, photophysical properties, and terahertz (THz) spectra. Time-dependent density functional theory (TD-DFT) shows that the luminescence performance of these complexes is attributed to the metal-to-ligand charge transfer (MLCT) in combination with ligand-to-ligand charge transfer (LLCT). In complexes 1–3, the characteristic peak at 1.4 THz is mainly related to the C–H⋯π interaction formed by the H atom on the 4#/5# position of 2, 3- f and the benzene ring from the bdppmapy on the adjacent asymmetric unit. The common C–H⋯π interaction enhances the rigidity of the structure and has non-negligible influence on the photoluminescence quantum yields (PLQYs): the stronger the C–H⋯π interaction is, the higher the quantum yield (QY) is. In complexes 4–6, similar absorption peaks (1.10–1.30 THz) are mainly related to the C–H⋯π interactions, and strong absorption peaks (1.50–1.90 THz) are affected by the typical hydrogen bonds N–H⋯F/O and O–H⋯O. These results show that some weak interactions can be characterized by THz time-domain spectroscopy (THz-TDS). So, the THz spectroscopy method would make it possible to tune some of the weak interactions in complex structures to regulate the luminescence of materials.